Effect of an inhaled neutral endopeptidase inhibitor, phosphoramidon, on baseline airway calibre and bronchial responsiveness to bradykinin in asthma. Issue 5 (May 1995) - Crimi, N; Polosa, R; Pulvirenti, G; Magrì, S; Santonocito, G; Prosperini, G; Mastruzzo, C; Mistretta, A
Abstract : BACKGROUND–Bradykinin is a potent vasoactive peptide which has been proposed as an important inflammatory mediator in asthma since it provokes potent bronchoconstriction in asthmatic subjects. Little is known at present about the potential role of lung peptidases in modulating bradykinin-induced airway dysfunction in vivo in man. The change in bronchial reactivity to bradykinin was therefore investigated after treatment with inhaled phosphoramidon, a potent neutral endopeptidase (NEP) inhibitor, in a double blind, placebo controlled, randomised study of 10 asthmatic subjects. METHODS–Subjects attended on six separate occasions at the same time of day during which concentration-response studies with inhaled bradykinin and histamine were carried out, without treatment and after each test drug. Subjects received nebulised phosphoramidon sodium salt (10(-5) M, 3 ml) or matched placebo for 5-7 minutes using an Inspiron Mini-neb nebuliser 5 minutes before the bronchoprovocation test with bradykinin or histamine. Agonists were administered in increasing concentrations as an aerosol generated from a starting volume of 3 ml in a nebuliser driven by compressed air at 8 1/min. Changes in airway calibre were measured as forced expiratory volume in one second (FEV1) and responsiveness as the provocative concentration causing a 20% fall in FEV1 (PC20). RESULTS–Phosphoramidon administration caused a transient fall in FEV1 from baseline, FEV1 values decreasing 6.3% and 5.3% on the bradykinin and histamine study days, respectively. When compared with placebo, phosphoramidon elicited a small enhancement of the airways response to bradykinin, the geometric mean PC20 value (range) decreasing from 0.281 (0.015-5.575) to 0.136 (0.006-2.061) mg/ml. In contrast, NEP blockade failed to alter the airways response to a subsequent inhalation with histamine, the geometric mean (range) PC20 histamine value of 1.65 (0.17-10.52) mg/ml after placebo being no different from that of 1.58 (0.09-15.21) mg/ml obtained after phosphoramidon. CONCLUSIONS–The small increase in bronchial reactivity to bradykinin after phosphoramidon exposure suggests that endogenous airway NEP may play a modulatory role in the airways response to inflammatory peptides in human asthma.